Проверка состояния системы уравнивания потенциалов энергообьектов - Глебов, Олег Юрьевич; Киприч, Светлана Викторовна; Колиушко, Георгий Михайлович; Пличко, Андрей Валерьевич (НТУ "ХПИ", 2016)
Приведены основные требования нормативных документов, предъявляемые к основной и дополнительной системам уравнивания потенциалов (СУП). Показано, что можно использовать в качестве защитных проводников СУП, их сечение, каким образом прокладывать и выполнять соединение и присоединение защитных проводников. Приведен перечень документов, передаваемых монтажной организацией при передаче электроустановки в эксплуатацию, содержание паспорта на заземляющее устройство (ЗУ) электроустановок. Описаны мероприятия, предназначенные для проверки состояния СУП. Приведены примеры проведения проверок СУП. Сформулированы основные недостатки выполнения СУП. Основной вывод: проверку состояния СУП целесообразно совмещать с проверкой ЗУ и СМЗ.

The basic regulatory requirements imposed on the main and additional equipotential bounding systems (EBS) is shown in the article. It is shown: what exactly can be used as protective conductors of these systems, what should be their cross section, how to lay and carry out the connection of protective conductors. It is given a list of the documents transmitted by the installer organization to maintenance of electrical installations, also a content of the grounding system passport. The activities directed to test of EBS, which include: visual inspection; checking structural condition; measurement of the contact connections resistance between the grounding element and an element of EBS are described. Examples of EBS inspections are given. The basic disadvantages of the implementation of EBS is formulated. The main conclusion: testing of the equipotential bounding systems it is advisable to combine with testing of the grounding system and lightning protection systems.
Verification of the state of equipotential bounding systems on power industry object
Keywords: электробезопасность; заземление; испытание электроустановок; системы выравнивания потенциалов; системы молниезащиты; electrical safety; grounding